Belles Lettres and Historical Fact: Fiction as a Symbol and Source in Writing on Russian and Central European History - Winklerová, Martina (Dějiny – teorie – kritika, 2024)
This article is concerned with the historical construction of images of Russia and Central Europe through fiction and looks at the pitfalls of using fiction as a historical source. In addition, the author uses concrete examples to consider Russian and Central European novelists´ interest in history and to analyse the way they perceive the past. She is critical of the fragmentary fashion in which Western historians use images of Russian life in Russian fiction, sometimes oversimplifying and distorting. At the same time she raises a basic question for the image of the past: how was fiction read at the time of its writing and how has fiction been used in the framework of social and cultural communication. At the theoretical level, she reaches the conclusion that historians will have to create their own methods, distinct from the methods of literary critics, for establishing the importance that fiction had at a particular time, in a particular political situation and within a certain social class or group.